EFEKTIVITAS PENGELOLAAN DANA DESA DI DESA TAMALANREA, KECAMATAN BONTOTIRO, KABUPATEN BULUKUMBA - Audia, Winda; Natsir, Uhud Darmawan; Ramli, Anwar; Sahabuddin, Romansyah; Akbar, Abdi (Jurnal Manajemen, 2024)
The purpose of this study was to determine the effectiveness of managing village funds in Tamalanrea Village, Bontotiro District, Bulukumba Regency. This type of research is descriptive qualitative (case study). The source of this research data is the Village Fund Budget Realization Report. The results of this study indicate that the results of this study indicate that Village Fund Allocation Management is effective in increasing village development in Tamalanrea Village, Bontotiro District, Bulukumba Regency. In addition, there are inhibiting factors in the form of human resources who do not understand and participate in the village fund allocation management process